The Role of Science of Counselling for Adolescent Mental Health - Agustiningsih; Shanti Wardaningsih (Postgraduate, University of Mataram, 2025)
Adolescence is faced with the problem of self-mastery or self-control. Juvenile delinquency is a form of conflict that is not resolved properly in childhood, so that the adolescent phase fails to undergo the process of mental development. This condition is called adolescents experiencing mental health problems. This research uses the narrative literature review method. The narrative literature review method is one method for conducting a qualitative literature review. This method aims to compile a review or summary of the results of previous research on a particular topic. This method is commonly used to examine or analyse a previous study and then create and package it in the latest version. Therefore, the author chose this method because it is in accordance with the purpose of making this research to examine and compare previous research with the current novelty. Based on the articles that have been obtained 6 articles related to the effect of peer counselling on empathy and mental health. Teenagers tend not to want to tell when they are experiencing difficulties. Peer counselling is an effort to increase empathy because students will easily share their complaints, because they have trust in their peers. Adolescents are also vulnerable to mental health problems in adolescents such as the development of various biological (physical), cognitive and socioemotional domains.